Pharmacotherapeutic characteristics of the combination of phloroglucinol and simethicone in the context of the treatment of spastic conditions of the gastrointestinal tract (literature review) - L.B. Bondarenko; N.O. Gorchakova; O.K. Biloshitska; O.Ya. Bespalova (Journal of V. N. Karazin Kharkiv National University: Series Medicine)
Background. Spastic conditions of the gastrointestinal tract, such as irritable bowel syndrome, significantly reduce patientsʼ quality of life, create substantial socio-economic burden, and are a common reason for seeking medical care. The lack of a universal therapy, the complexity of the pathogenesis, and individual patient responses to treatment necessitate new approaches to pharmacotherapy. One promising direction is the use of a combination of phloroglucinol and simethicone.